2
$\begingroup$

The Wiki page on Twin Primes says

The pair $(m, m+2)$ is twin prime, iff $4((m-1)! + 1) \equiv -m \pmod {m(m+2)}$.

This is obviously connected to Wilson's Theorem. Can anybody provide a proof for that, along the lines of thought given here, Wilson's Theorem/Proofs/Prime modulus – another proof?

$\endgroup$
  • 4
    $\begingroup$ Use Chinese Remainder theorem. If $m$ is odd, then the right condition is equivalent to two formulas: $4((m-1)!+1) \equiv 0 \pmod m$ and $4((m-1)!+1)\equiv -2 \pmod {m+2}$. The case where $m$ is even needs to be dealt with separately. $\endgroup$ – Thomas Andrews May 14 '12 at 19:43
6
$\begingroup$

By Wilson's Theorem, if $m$ is prime, then $(m-1)!+1\equiv 0\pmod{m}$, and therefore $$4[(m-1)!+1]+m \equiv 0\pmod{m}.\tag{$1$}$$

If $m+2$ is prime, then $(m+1)!+1\equiv 0\pmod{m+2}$, again by Wilson's Theorem. But since $m+1\equiv -1\pmod{m+2}$, and $m\equiv -2\pmod{m+2}$, we have $(m+1)!\equiv (-1)(-2)(m-1)!\equiv 2(m-1)!\pmod{m+2}$, and therefore $$4[(m-1)!+1]+m \equiv 2(m+1)!+2+m+2\equiv 0\pmod{m+2}.\tag{$2$}$$ Since $m$ is odd, the numbers $m$ and $m+2$ are relatively prime, and therefore by $(1)$ and $(2)$ we have $4[(m-1)!+1]+m\equiv 0\pmod{m(m+2)}$.

The proof of the converse follows similar lines, this time using the fact that the Wilson condition is sufficient for primality.

$\endgroup$
  • $\begingroup$ Very nice. Not along the lines I asked for, but (even better) I learnt something else. Thank you. $\endgroup$ – draks ... May 14 '12 at 21:43
3
$\begingroup$

Hint $ $ Both directions can be quickly and easily proved simultaeneously using Wilson's theorem:

$$\begin{eqnarray} \rm m\ prime &\iff&\rm\ mod\ m\!:\ &\rm\: 1+(m\!-\!1)! \equiv 0\iff 4(m\!-\!1)!+4\equiv 0\equiv -m \\[.2em] \rm m\!+\!2\ prime &\iff&\rm mod\ m\!+\!2\!:\ &\rm\: 1+(m\!+\!1)!\equiv 0\iff 4(m\!-\!1)!+4 \equiv 2\equiv -m\\[.2em] \rm & &\rm because &\rm \!\!\!\!2(1+\color{#c00}{(m\!+\!1)!})\:\ \equiv \:\ 2\: +\: 4\color{#c00}{(m\!-\!1)!} \\[.2em] & &\rm because &\rm\qquad\! \color{#c00}{(m\!+\!1)!} = \underbrace{(m\!+\!1)m}_{\large\equiv\ -1\,(-2) }(m\!-\!1)!\equiv \color{#c00}{2(m\!-\!1)!}\\ \end{eqnarray}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.